2012
DOI: 10.1073/pnas.1207767109
|View full text |Cite
|
Sign up to set email alerts
|

Role of pro-brain-derived neurotrophic factor (proBDNF) to mature BDNF conversion in activity-dependent competition at developing neuromuscular synapses

Abstract: Formation of specific neuronal connections often involves competition between adjacent axons, leading to stabilization of the active terminal, while retraction of the less active ones. The underlying molecular mechanisms remain unknown. We show that activitydependent conversion of pro-brain-derived neurotrophic factor (proBDNF) to mature (m)BDNF mediates synaptic competition. Stimulation of motoneurons triggers proteolytic conversion of proBDNF to mBDNF at nerve terminals. In Xenopus nerve-muscle cocultures, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 55 publications
6
129
0
Order By: Relevance
“…ProBDNF/p75 NTR signaling was an attractive candidate since it has been shown to retrogradely depress synapses in an activity-dependent manner (neuromuscular junction: Yang et al, 2009a;Je et al, 2012;hippocampus: Woo et al, 2005;Yang et al, 2014). Furthermore, it is highly expressed during development in the hippocampus (Yang et al, 2009b), and it is known to be involved in synaptic competition and elimination (Je et al, 2012). To test the role of proBDNF/p75 NTR signaling in local plasticity and synaptic clustering, we first investigated whether synaptic depression induced by asynchronous stimulation (see : stimulation is triggered in response to distant spontaneous synaptic activity (12-24 mm) to decrease the local coactivity rate.…”
Section: Depression Of Locally ''Out-of-sync'' Synapses Is a General mentioning
confidence: 99%
“…ProBDNF/p75 NTR signaling was an attractive candidate since it has been shown to retrogradely depress synapses in an activity-dependent manner (neuromuscular junction: Yang et al, 2009a;Je et al, 2012;hippocampus: Woo et al, 2005;Yang et al, 2014). Furthermore, it is highly expressed during development in the hippocampus (Yang et al, 2009b), and it is known to be involved in synaptic competition and elimination (Je et al, 2012). To test the role of proBDNF/p75 NTR signaling in local plasticity and synaptic clustering, we first investigated whether synaptic depression induced by asynchronous stimulation (see : stimulation is triggered in response to distant spontaneous synaptic activity (12-24 mm) to decrease the local coactivity rate.…”
Section: Depression Of Locally ''Out-of-sync'' Synapses Is a General mentioning
confidence: 99%
“…37,38 Furthermore, some of the candidate proteins that are implicated in schizophrenia have functional connections with either MMP-9 or MMP-9-interacting proteins, such as brain-derived neurotrophic factor (BDNF) and N-methyl-D-aspartate (NMDA) receptors, among others. 39,40 Another hallmark of schizophrenia is the dysfunction of dendritic spines. Several studies reported a reduction of spine density in cortical pyramidal neurons in schizophrenia (for review, see Moyer et al 41 ).…”
Section: Mmp-9 In Schizophreniamentioning
confidence: 99%
“…Nevertheless, the stabilization of the NMJ involves a synaptic competition that would be mediated by a ''punishment'' or Mechanisms controlling neuromuscular ''elimination'' signal produced by the post-synaptic cell, which causes the retraction of some of the terminals, as well as a ''protective'' or ''reward'' signal that stabilizes one terminal [70]. A hypothesis to explain synapse elimination has been the active versus inactive synapses involving a competitive process.…”
Section: Underlying Possible Mechanisms In the Regulation Of Nmj Stabmentioning
confidence: 99%
“…Whereas molecular cues involved in this process have remained poorly characterized so far, it has been recently shown that the activity-dependent conversion of pro-brainderived neurotrophic factor (proBDNF) to mature (m)BDNF mediates synaptic competition [70]. The activity of motor neurons will trigger the proteolytic conversion of proBDNF to mBDNF at nerve terminals whose respective roles are opposite: when two distinct motor neuron axons innervate one myocyte, proBDNF-p75(NTR) signaling promotes the retraction of the less active terminal, whereas mBDNF-tyrosine-related kinase B (TrkB) p75NTR facilitates the stabilization of the more active one.…”
Section: Underlying Possible Mechanisms In the Regulation Of Nmj Stabmentioning
confidence: 99%